Pengembangan Lembar Kegiatan Peserta Didik Praktikum Akuntansi Perusahaan Manufaktur Berbasis Contextual Teaching And Learning (CTL) Di SMK - Nanik Saruati; Joni Susilowibowo (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
One component that cannot be separated in the learning process is teaching material. In general, the use of teaching materials by teachers and students to practice working on questions is the Student Activity Sheet. In the current curriculum, the 2013 curriculum students are required to be able to think critically and creatively in learning. In supporting learning systems that are in accordance with the curriculum, contextual teaching and learning based learning is implemented where students learn by connecting material with other things in real life. This study aims to develop teaching materials, namely Contextual Teaching and Learning based Student Activity Sheets on the accounting practicum subjects of manufacturing companies in Vocational Schools, and analyze the results of the feasibility of LKPD. The researcher chose the 4D development model from Thiagarajan, but this research was not carried out until the deployment stage, but only to the development stage. The subjects in this study were material experts from accounting education lecturers and teachers in vocational schools, Indonesian language lecturers and education technology lecturers. The subject is 3 experts namely material experts, graphic experts, and linguists who will assess the feasibility of LKPD. The validation results show the results of the material experts with a score of 88.5%, the validation of the linguist 98.7% and the validation of the graphic expert 86.5% so that an average score of 91.2% is obtained so that it can be concluded that the development of the Practicum Student Activity Sheet accounting manufacturing company class XII accounting in vocational schools is proper to be used as a support for teaching materials in the subjects concerned in the teaching and learning process.